Plasma meets metamaterials: Three ways to advance space micropropulsion systems. Issue 1 (1st January 2021) - Levchenko, Igor; Xu, Shuyan; Cherkun, Oleksii; Baranov, Oleg; Bazaka, Kateryna
ABSTRACT: Plasma and metamaterials: what new advances in space micro-propulsion systems can they bring when used together? The aim of this concise review article is to attract attention of the space propulsion scientists and engineers, along with experts working in the fields of micro-machines, optics, communication, and other hi-tech devices, to the opportunities that arise from different possible combinations of plasma and metamaterials. Along with plasma-based techniques used for the fabrication of complex metamaterials, we examine two unusual plasma/metamaterial systems, namely when plasma interacts with a metamaterial, and when plasma itself features some properties of a metamaterial. The fundamental physics behind the principal processes that define the behavior of these systems is briefly outlined. Possible applications in space technology, mainly for micro-propulsion systems for Cubesats and small satellites are also sketched. Abstract : uf0001